Comments on and illustrations of the WFUMB CEUS liver guidelines: Rare malignant neuroendocrine and predominant epithelioid liver lesions - Zadeh, Ehsan Safai; Huber, Katharina Paulina; Görg, Christian; Möller, Kathleen; Jenssen, Christian; Lim, Adrian; Taut, Heike; Dong, Yi; Cui, Xin Wu; Dietrich, Christoph F. (Medical ultrasonography, 2024)
The diagnosis or rare, non-hematologic malignant lesions of the liver may be a challenge owing to the rarity of the disease, and is usually made by histological confirmation. Ultrasound with color Doppler and contrast-enhanced, if required, taking into account the clinical background of the patient, may help to focus the differential diagnosis. In this review, we describe the pathological and ultrasound features of rare malignant neuroendocrine and predominantly epithelioid liver lesions including primary neuroendocrine tumor of the liver, Invasive mucinous cystic neoplasm of the liver, and also hepatoblastoma.